Population density of Sotalia guianensis (Cetacea: Delphinidae) in the Cananéia region, Southeastern Brazil - Liisa Havukainen; Emygdio Leite de Araujo Monteiro Filho; Gislaine de Fatima Filla (Revista de Biología Tropical, 2011)
Population density in cetaceans can be estimated through photo-identification, mark-recapture, land-based observations and visual estimative. We the aim to contribute with conservation strategies, we used line transects (distance method) to estimate the population density of the river dolphin, S. guianensis, in the estuarine region of Cananéia, Southeastern Brazil. The study, developed from May 2003 until April 2004, during dry and rainy seasons and different times of the day, included a sampling area divided into three sectors according to their proximity to the open sea: Sector I (the closest to the open sea); Sector II (with a large flow of fresh water and a salient declivity); and Sector III (with a large flow of fresh water and non salient declivity). Onboard random sampling was carried out in all three sectors, and dolphins seen from the bow to 90° on both port and starboard sides, were registered along with their position and distance from the boat. The total density found was 12.41ind/km² (CV=25.53%) with an average of 2.2 individuals per group for both periods of the day, morning and afternoon. Densities also varied between dry and rainy seasons, being lower in the first with 5.77ind/km² (CV=27.87%) than in the second 20.28ind/km² (CV=31.95%), respectively. Regarding the three sectors, a non-causal heterogeneous distribution was found: Sector I was the most populated (D=33.10ind/km², CV=13.34%), followed by Sector II (D=7.8ind/km², CV=21.07%) and Sector III (D=3.04ind/km², CV=34.04%). The aforementioned area, due to its proximity to the open sea, has the highest salinity level and therefore has the greatest chance of holding most of the marine fish schools which can be cornered by dolphins on high declivity areas during fishing activities. This suggests that food availability may be the most important factor on the river dolphin’s distribution in the estuary. Similar studies will contribute to a better understanding of these populations and are essential for future conservation strategies. Rev. Biol. Trop. 59 (3): 1275-1284. Epub 2011 September 01. El delfín estuarino S. guianensis, habita en aguas tropicales costeras y estuarinas. A pesar de su amplia distribución no se conoce suficiente, por lo tanto, recientemente se han intensificado sus estudios poblacionales. Transectos de línea (Método Distancia) fueron utilizados para estimar la densidad de población de S. guianensis en la Bahía Trapandé, región de estuario de Cananéia, Sudeste de Brasil. El muestreo aleatorio se realizó en tres sectores de la bahía desde mayo 2003 hasta abril 2004. La densidad total fue de 12.41ind/km2. Considerando los tres sectores de forma individual, se observó una distribución heterogénea no ocasional: Sector I (más cerca del mar abierto) D=33.10ind/km2; Sector II (que recibe un gran flujo de agua dulce, con un declive más destacado) D=7.80ind/km2; Sector III (que recibe un gran flujo de agua dulce, sin declives salientes) D=3.04ind/km2. Las condiciones ambientales como la estación de lluvias y la estacionalidad diaria, también se observaron en esta bahía. Los resultados mostraron un uso heterogéneo de la zona por los delfines